Experimental study into rotational-oscillatory vibrations of a vibration machine platform excited by the ball auto-balancer - Volodymyr Yatsun (Eastern-European Journal of Enterprise Technologies, 2018)
We have experimentally investigated the rotational-oscillatory vibrations of vibratory machine platform excited by the ball auto-balancer.